Foundation analysis and design - Bowles, Joseph E. (McGraw-Hill, 1996)
Introduction; Geotechnical and index properties: laboratory testing; settlement and strength correlations; Exploration, sampling and in situ soil measurements; Bearing capacity of foundations; Foundation settlements; Improving site soils for foundation use; Factors to consider in foundation design; Spread footing design; Special footings and beams on elastic foundations; Mat foundations..